Anti-LSP antibodies in acute liver disease. Issue 7 (July 1982) - Meliconi, R; Perperas, A; Jensen, D; Alberti, A; McFarlane, I G; Eddleston, A L; Williams, R
Abstract : Sera from 71 patients with acute liver injury have been tested for antibodies to hepatocyte membrane lipoprotein complex (LSP) using a sensitive radioimmunoassay. Two main patterns of anti-LSP response were seen. In the first, seen in patients with type A and B viral hepatitis, anti-LSP antibodies were detectable at presentation, with the highest titres two to 10 days before the peak in serum aminotransferases and, in the hepatitis B patients, when viral DNA polymerase concentrations were still high, indicating active viral replication. These findings are consistent with the anti-LSP response being consequent on an interaction between T cells and neoantigens on the liver cell surface. A similar pattern was found in halothane hepatitis where immune responses to a halothane-altered liver membrane antigen are present early in the course of the disease. In the second type of response, exemplified by cases with paracetamol-induced hepatic necrosis, anti-LSP was only occasionally detectable at presentation, although present in very low titre later in the clinical course. This may be due to the release of altered antigen at the time of hepatocellular injury. The same pattern was found in a selected group of patients with uncomplicated acute alcoholic hepatitis, suggesting that in both these groups of patients the liver damage may have been due to a direct toxic effect on liver cells.